PATTERNS OF TREATMENT OF COMBINED BURN EYE INJURIES IN PATIENTS HOSPITALIZED IN BURN UNITS - E. V. Chentsova; P. V. Makarov; A. N. Verigo; A. O. Petrova; S. V. Smirnov (Российский офтальмологический журнал, 2018)
The paper is focused on combined burn injuries of the eye, face and other body parts in acute care patients treated in non-ophthalmic hospital departments. Purpose: to develop patterns of actions by ophthalmologists and burn doctors at various stages of multiple burn injuries in patients treated in burn units. Materials and methods. 158 burn patients were given full clinical and instrumental examination. Group 1 included 95 patients hospitalized in the department of eye traumatology and reconstructive surgery after being treated in burn units elsewhere, while group 2 consisted of 63 patients examined and treated simultaneously by ophthalmologists and burn doctors from the start of admission to burn units. Results. The patients in Group 1 developed serious ophthalmic complications, ranging from ulceration or perforation of outer eye coats, swollen cataracts, hypopyon, cicatricial eyelid deformation, lagophthalmos etc. to eye apple atrophy, all caused by the absence of eye surgery assistance at early stages of burn treatment. Conclusion. The proposed patterns and range of surgical assistance including that given in the early stages of treatment, prevented the development of severe complications to the eye and the annexa, reduced the rehabilitation period and improved the functional prognosis of combined burn eye injuries. For citation: Chentsova E.V., Makarov P.V., Verigo Е.N., Petrova A.O., Smirnov S.V. Patterns of treatment of combined burn eye injuries in patients hospitalized in burn units. Russian ophthalmological journal. 2018; 11 (3): 37-42 (In Russian). doi: 10.21516/2072-0076-2018-11-3-37-42